Pengaruh Model Pembelajaran Jigsaw Terhadap Hasil Belajar IPS Materi Interaksi Sosial di SD Negeri 4 Srobyong - Fauzia, Septiana Nur; Anintyawati, Riska (Indo-MathEdu Intellectuals Journal, 2025)
The teaching of Social Science (IPS) that is still monotonous and teacher-centered can impact the low learning outcomes of students, especially in the material of Social Interaction. Therefore, a learning model is needed that can enhance student engagement and understanding. The purpose of this research is to determine the effect of the jigsaw learning model on the learning outcomes of students in the 5th-grade IPS subject. This type of research is a quasi-experiment with a nonequivalent control group design. The population consists of 40 fifth-grade students. The sampling technique used is purposive sampling. The research sample includes class V A (experimental group) with 20 students and class V B (control group) with 20 students. Data collection is done through tests that are validated for validity and reliability. Prerequisite tests use normality and homogeneity tests. Data analysis uses t-tests. The research results indicate that the average posttest score of the experimental group is 81.54, while the posttest score of the control group is 72.79. In addition, the t-test results show 0.000 < 0.05. This means that there is a significant difference between the pretest-posttest results of the experimental group using the jigsaw learning model and the control group using the conventional learning model. Therefore, it is concluded that there is an effect of using the jigsaw learning model on the learning outcomes of social studies in the social interaction material at SD Negeri 4 Srobyong